Effectiveness Criteria for Interaction Between the Participants of the Educational Production Cluster Within PDA - Lizunkov, Vladislav G.; Morozova, Marina V.; Zakharova, Alexandra A. (International Journal of Emerging Technologies in Learning (iJET), 2021)
The current context of the Priority Development Areas (PDA) raises the issues of ensuring the interaction between vocational and higher education organizations and real sector enterprises operating in the city. This paper presents an analysis of Russian and foreign studies to identify the main stakeholders interested in this interaction, as well as the criteria that contribute to determining the effectiveness of joint work to train qualified personnel demanded by the PDA production enterprises.